Mountain waves over northeast India and neighbouring regions - DE, U.S. (MAUSAM, 1971)
Theoretical computations of the wave lengths of mountain waves have been made from the available wind and temperature data over northeast India and neighbouring regions. The results have been compared with the observational data and have been found to agree with them.